Perhitungan Break Even Point (BEP) sebagai Strategi Pengendali Keuangan pada UMKM Desa Wisata Curug, Kabupaten Bogor - Rr Yoppy Palupi Purbaningsih (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This community service activity aims to improve the financial literacy of Micro, Small, and Medium Enterprises (MSMEs) through targeted training in calculating the Break Even Point (BEP) as a financial control tool. BEP, or break-even point, is the specific point at which total revenue equals total costs, allowing businesses to determine the minimum sales volume required to avoid losses. The activity was held in the Curug Tourism Village in Bogor Regency, with 27 MSMEs from various business sectors actively participating. The implementation method included outreach, training sessions, practical BEP calculations using participants' actual business data, and post-training mentoring to ensure long-term learning. The results of the activity demonstrated a significant improvement in participants' understanding of the BEP concept and its practical application in determining selling prices, production volumes, and cost control. Therefore, the application of BEP analysis is a crucial and effective strategy in supporting the sustainability and operational efficiency of MSME businesses.